Indirect Electrochemical Determination of Ribavirin Using Boronic Acid-Diol Recognition on a 3-Aminophenylboronic Acid-Electrochemically Reduced Graphene Oxide Modified Glassy Carbon Electrode (APBA/ERGO/GCE). (13th August 2019) - Wang, Xiaoyan; Shen, Weiyang; Zhang, Xiaolei; Guo, Siyan; Gao, Ye; Li, Xiaotong; Feng, Fang; Yang, Gongjun
Abstract: A novel method for the indirect electrochemical determination of ribavirin based on boronic acid-diol recognition was developed using the platform as the sensing element. The device was constructed using a 3-aminophenylboronic acid (APBA)-electrochemically reduced graphene oxide (ERGO) modified electrode. When the electrode was immersed in a solution of ribavirin, complexation of boronic acid groups of APBA with ribavirin occurred at the surface of the electrode and simultaneously caused steric hindrance, resulting in a current decrease because the ferricyanide redox probe was unable access the surface. Under the optimized conditions, a linear relationship was obtained between the relative change in current (%Δ i ) of [Fe(CN)6 ] 3−/4− and the concentration of ribavirin at levels from 10.0 to 7.50 × 10 2 ng mL −1 . The proposed electrochemical sensor performed with acceptable sensitivity and reproducibility and was successfully used to determine the content of ribavirin in an injection with satisfactory results.